PENGARUH FERMENTASI BUNGKIL INTI KELAPA SAWIT MENGGUNAKAN ISOLAT BAKTERI SELULOLITIK DARI BELALANG KEMBARA (Lokusta migratoria L.) DALAM PAKAN TERHADAP PENAMPILAN PRODUKSI PUYUH JANTAN - , ARIF PRANATA, Prof. Dr. Ir. Lies Mira Yusiati, S.U. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This experiment was conducted to evaluate the nutritional value of Palm Kernel Cake (PKC) Fermented by cellulolitycs bacterial from grasshoper and the effect of the utilization fresh and Fermented Palm Kernel Cake (FPKC) in Quail (Cortunix-cortunix japonica) diets on growth performance. Cellulolytic bacterial have been isolated from the gut of grasshoper and the bacterial growth was optimized on the different medium pH (4, 4.5, 5, 5.5, 6, 6.5), temperature (25, 30, 35, and 40oC) and incubation time (1â6 day). The experiment effect of fermentation using cellulolitycs bacterial were designed in 3 treatment and 3 replication. The treatment were 0% (control) was fermentation without cellulolitycs bacterial, 10, 20, and 30% treatment with addition 10, 20, and 30% cellulolitycs bacterial. 210 male day old quail were randomly devide in to seven diets treatment in 3 replications with 10 male quail. The dietary treatments were K (kontrol), NF10, NF20 and NF 30 diets with addition 10, 20, and 30% PKC, F10, F20, and F30 diets with addition 10, 20, and 30% FPKC. ME and CP of feed formulation was 2900 kcal/kg and 22%. The data collected were microbial growth based on optical density (OD) and CMC-ase activity, fiscal and chemical quality of FPKC, and performance of quail and will be analyzed by a one way classification of variance analysis (CRD), followed by testing the significant mean by Duncanâs new multiple range test (DMRT). The result showed the optimum bacterial growth was on pH 5.5, incubation temperature 30oC and days 2 incubation. Dry matter (DM), organic matter (OM), ash, crude protein (CP) dan ether extract (EE) had not significant different and crude fibre (CF) had significant different 26.53, 23.73, 20.62, 20.73%. Metabolized energy had significant differences 1739.696, 1776.116, 1873.384 dan 2014.888 kcal/kg. Feed consumption 68.50, 77.00, 80.08, 73.88, 80.43 and 82.62 (g/quail/week), feed convertion 2.86, 2.81, 3.38, 3.17, 3.13, 3.28 dan 3.31, and the treatment had no effect on body weight and carcass percentation. It was conclude that fermentation using cellulolitycs bacterial from grasshoper could increase the nutritional value of FPKC and additions 10% of FPKC on diets had no negative effect on quail performance.